Role of sphingosine kinase 1 and sphingosine‐1‐phosphate in CD40 signaling and IgE class switching. Issue 10 (1st July 2014) - Kim, Eugene Y.; Sturgill, Jamie L.; Hait, Nitai C.; Avni, Dorit; Valencia, Evelyn C.; Maceyka, Michael; Lima, Santiago; Allegood, Jeremy; Huang, Wei‐Ching; Zhang, Shijun; Milstien, Sheldon; Conrad, Daniel; et al.
Abstract : The tumor necrosis factor (TNF) receptor family member CD40 plays an essential role in the activation of antigen‐presenting cells, B cell maturation, and immunoglobulin (Ig) class switching critical for adaptive immunity. Although the bioactive sphingolipid metabolite sphingosine‐1‐phosphate (S1P) and the kinase that produces it, sphingosine kinase 1 (SphK1), have long been implicated in the actions of TNF mediated by engagement of TNFR1, nothing is yet known of their role in CD40‐mediated events. We have now found that ligation of CD40 activates and translocates SphK1 to the plasma membrane, leading to generation of S1P. SphK1 inhibition in human tonsil B cells, as well as inhibition or deletion of SphK1 in mouse splenic B cells, significantly reduced CD40‐mediated Ig class switching and plasma cell differentiation ex vivo. Optimal activation of downstream CD40 signaling pathways, including NF‐κB, p38, and JNK, also required SphK1. In mice treated with a SphK1 inhibitor or in SphK1 –/– mice, isotype switching to antigen‐specific IgE was decreased in vivo by 70 and 55%, respectively. Our results indicate that SphK1 is important for CD40‐mediated B cell activation and regulation of humoral responses and suggest that targeting SphK1 might be a useful therapeutic approach to control antigen‐specific IgE production.—Kim, E. Y., Sturgill, J. L., Hait, N. C., Avni, D., Valencia, E. C., Maceyka, M., Lima, S., Allegood, J., Huang, W.‐C., Zhang, S., Milstien, S., Conrad, D., Spiegel, S., Role of sphingosine kinase 1 and sphingosine‐1‐phosphate in CD40 signaling and IgE class switching. FASEB J. 28, 4347–4358 (2014). www.fasebj.org